Edible Mushrooms: Management of Diabetes Mellitus and Phytochemical Screening of Agaricus Bisporus - Varun Mishra; Sarbjot Singh; Rajneesh Kaur; Brij Bhushan; Shruti Jaswal; Anita Devi; Anuneet Kaur (International Journal of Cell Biology and Cellular Functions, 2025)
A metabolic disease characterized by elevated blood glucose levels; diabetes mellitus affects millions of people. If not treated on time, it causes problems, damage organs, and even life-threatening. Studies have shown that diabetes can be avoided and controlled with a healthy lifestyle that incorporates exercise and a balanced diet. While there are several synthetic medications available to treat this illness using them over an extended period of time is linked to a number of negative effects. As a result, researchers are paying more attention to medicinal plants and herbs since they are seen as a safer option. Edible mushrooms are a type of plant-based therapy that may help with diabetes. They are rich in natural compounds, like fibers, polysaccharides, phenolics, and alkaloids, and have long been known for their anti-diabetic, antioxidant, and cholesterol-lowering properties. The carbohydrates in mushrooms act as prebiotics, helping to change gut bacteria composition and reduce insulin resistance. The etiology of diabetes is covered in this review, along with an explanation of a few possible mushroom species with anti-hyperglycemic properties. It has also been studied how various polysaccharides found in mushrooms affect the composition of gut macrobiotic in animal models of diabetes.
Keywords: Cellular processes; Diabetes mellitus; Metabolic; Mushrooms; T cells; β-cells